If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + 6 = 6(x + -1) + -3x Reorder the terms: 6 + 3x = 6(x + -1) + -3x Reorder the terms: 6 + 3x = 6(-1 + x) + -3x 6 + 3x = (-1 * 6 + x * 6) + -3x 6 + 3x = (-6 + 6x) + -3x Combine like terms: 6x + -3x = 3x 6 + 3x = -6 + 3x Add '-3x' to each side of the equation. 6 + 3x + -3x = -6 + 3x + -3x Combine like terms: 3x + -3x = 0 6 + 0 = -6 + 3x + -3x 6 = -6 + 3x + -3x Combine like terms: 3x + -3x = 0 6 = -6 + 0 6 = -6 Solving 6 = -6 Couldn't find a variable to solve for. This equation is invalid, the left and right sides are not equal, therefore there is no solution.
| 5X+4-6=2 | | -2(-6-7n)+5=145 | | 5*3x+8=4(25) | | 25-[2+9y-3(y+5)]=-4(4y-7)-[8(y-1)-15y+22] | | -6p+8p=16+4p | | 1.3(-2)-5.6= | | 3*3x+8=4(15) | | 26-1[1+6y-4(y+4)]=-5(3y-3)-[8(y-1)-18y+4] | | 1.3(4.3)-5.6= | | 5(2d-3)-4d=2(4-d)-15 | | 8x+8x+15x+15x=230 | | log(35/2x)=1 | | 3w+1=10w+1-7w | | 3j-10=50 | | (-2x-3)(2x-1)=(x+4)(2x-1) | | (x+2)+(3x-2)+(2y+1)+(2x-3)=360 | | 2v+3= | | 12m+144= | | 10x+0.5y+0.25z=100 | | 8.4+10= | | 2k-5=30 | | -35+9s=-4(5s-3) | | 11+2x-14=8x-3-6x | | (2w^3r^-2/5w^-2rz) | | 5+9x=5+12x-3x | | 10x-(7x+4)=8x | | 8x-4-2x=6x-4 | | -5(3-4a)=20 | | 1y=4x+283 | | 91375193459137451057+73452863568283456345384-661649589246861356218565= | | 6+2x=4x+8 | | 18x^2+8x-1=0 |